PENILAIAN KONDISI JALAN MENGGUNAKAN METODE SDI (SURFACE DISTRESS INDEX) DAN INVENTARISASI DALAM GIS (GEOGRAPHIC INFORMATION SYSTEM) DI KABUPATEN KLUNGKUNG - I Nyoman Yastawan; Dewa Made Priyantha Wedagama; I Made Agus Ariawan (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2021)
Assessment of road conditions using the SDI method and inventoried in the GIS in Klungkung Regency is carried out on the Jl. Gn Agung, Jl. Gn Rinjani, Jl. Gn Batukaru, Jl. Gn Semeru, and Jl. Gn Batur. Selection of district roads used by roads in the city of Semarapura which is the center of travel in Klungkung district should get more attention through road handling. In addition, the sections used are roads that visually have road damage. This research was conducted because there are still damaged roads that must be treated quickly. This study aims to analyze road conditions, analyze road handling types and inventory road conditions in a GIS map. The data used in this research are primary data and secondary data. Primary data was obtained through a survey of road conditions by measuring road damage, while secondary data was obtained from the Bina Marga section of the PUPRPKP Office of Klungkung Regency, namely, SK Klungkung regency roads, Klungkung regency road maps and Klungkung district road baseline data. The stages of research analysis were identification of road damage by measuring, data recapitulation by processing survey results, data analysis using the SDI method and inventorying in a GIS map. The results of the assessment for the Jl. Gn Agung is in moderate condition 0.416 km and slightly damaged condition is 0.300 km. Jl. Gn Rinjani, 0.277 km is slightly damaged. Jl. Gn Batukaru is slightly damaged by 0.119 km. Jl. Gn Semeru is slightly damaged by 0.288 km. Jl. Gn Batur condition is slightly damaged 0.546 km. For the type of handling carried out Jl. Gn Agung periodic maintenance and routine maintenance, Jl. Gn Rinjani, Jl. Gn Batukaru, Jl. Gn Semeru and Jl. Gn Batur is regular maintenance. Inventory of road condition data and basic road data of Klungkung district using GIS provides an overview of road conditions in the form of a road network map so as to provide convenience in monitoring road conditions and determining the type of handling. This research can be used as a reference in determining the type of handling of district roads in Klungkung district.